Gorilla - Browne, Anthony, 1946- (New York : Distributed by Random House, 1983)
Neglected by her busy father, a lonely young girl receives a toy gorilla for her birthday and together they take a miraculous trip to the zoo.
Publisher's Weekly.
School Library Journal.
Wilson's Children.
2.1
K-3.
K-3
Keywords: Fathers and daughters -- Fiction; Gorilla -- Fiction; Father-daughter relationship -- Fiction; Gorillas -- Fiction